Implementation of 16S rRNA Gene for Fish and Shrimp Barcoding in Mangrove Ecosystems in North Sumatra and Aceh, Indonesia - Hatika Hairani; Rizka Amelia; Ipanna Enggar Susetya; Arida Susilowati; Yuntha Bimantara; Tadashi Kajita; Mohammad Basyuni (Jurnal Ilmiah Perikanan dan Kelautan, 2023)
Highlight Research The genetic diversity of fish and shrimp from mangrove habitats was relatively substantial, with a heterozygosity of 0.926 and the exception of Langsa samples. AMOVA revealed that the diversity among individuals in the populations were higher compared to those within individuals. DNA barcode in mangroves is useful in developing mangrove conservation and restoration initiatives   Abstract Fish and shrimp are among the species that are vulnerable to high level of disturbance in mangrove ecosystem. This study aimed to investigate the implementation of 16S rRNA gene for fish and shrimp barcoding in mangrove ecosystems in North Sumatra and Aceh, Indonesia. 50 samples fresh fish and shrimp were collected from five mangrove ecosystems in North Sumatra, namely Belawan, Lubuk Kertang, Percut Sei Tuan, and Pulau Sembilan and Langsa of Aceh for DNA extraction process. The research was divided into four activities: sample collection, DNA isolation, PCR amplification, and data analysis. DNA was extracted using kit extraction (kit Reliaprep gDNA Tissue Miniprep System) and with PCR amplification. Genetic parameters were analyzed using Gen Alex 6.51 software and the relationship between sites was examined using the MVSP 3.22. The genetic diversity of fish and shrimp from mangrove habitats was relatively substantial, according to the findings, with a heterozygosity of 0.926, with the exception of Langsa samples, which were only identified in subclass A1. Genetic relationship between sites revealed that all samples clustered into two branches and were randomly dispersed within each site. This work confirmed the 16S rRNA gene worked for fish and shrimp barcoding in mangrove ecosystems, North Sumatra and Aceh, Indonesia and our findings are expected to be useful in developing mangrove conservation and restoration initiatives.